Retreatment with interferon plus ribavirin of chronic hepatitis C non-responders to interferon monotherapy: a meta-analysis of individual patient data. Issue 6 (1st December 2002) - Cammà, C; Bruno, S; Schepis, F; Lo Iacono, O; Andreone, P; Gramenzi, A G; Mangia, A; Andriulli, A; Puoti, M; Spadaro, A; Freni, M; Di Marco, V; et al.
Abstract : Background and aims: Retreatment with a combination of α interferon (IFN) plus ribavirin of patients with chronic hepatitis C who did not respond to IFN monotherapy has not been assessed in large controlled studies. Methods: To assess the effectiveness and tolerability of IFN/ribavirin retreatment of non-responders to IFN and to identify predictors of complete (biochemical and virological) sustained response, we performed a meta-analysis of individual data on 581 patients from 10 centres. Retreatment with various IFN schedules (mean total dose 544 mega units) and a fixed ribavirin dose (1000–1200 mg/daily depending on body weight) was given for 24–60 (mean 39.5) weeks. Results: Biochemical end of treatment and sustained responses were observed in 271/581 (46.6%; 95% confidence interval (CI) 42.6–50.7%) and in 109/581 (18.7%; 95% CI 15.6–22.0%) cases, respectively. Two hundred and six of 532 patients (38.7%; 95% CI 34.6–42.9%) had an end of treatment complete response to retreatment while a complete sustained response occurred in 88 of 559 (15.7%; 95% CI 12.8–18.8%). Fifty four of 581 patients (9.2%; 95% CI 7.0–11.7%) stopped retreatment due to adverse effects. By logistic regression, complete sustained response was predicted independently by age <45 years (p=0.04), by normal pretreatment γ-glutamyltransferase levels (p=0.01), and by a second course total IFN dose of at least 432 mega units (p=0.008). Conclusions: The overall low probability of effectiveness argues against indiscriminate retreatment of all IFN monotherapy non-responders with IFN/ribavirin. Patients less than 45 years old with normal γ-glutamyltransferase levels who were retreated with high dose long course combination therapy had a complete sustained response rate of 30%.